Prism Integrated Sdn Bhd (Shah Alam) / Muhammad Zulhilmi Syafiq Baharuddin - Baharuddin, Muhammad Zulhilmi Syafiq (Perpustakaan Tengku Anis, 2015)
Muhammad Zulhilmi Syafiq B. Baharuddin, number matric student 2012400096 is student from UiTM Kelantan branch, Machang campus was perform an internship at PRISM INTERGRATED SDN BHD for five month from 3 August 2015 until 31 December 2015. At PRISM, trainee has been teaching by each staff from each unit to do the work that has been given. Trainee was instructed according the duration of industrial training UiTM (August - December 2015). Each staff gives a lot of useful information and knowledge to the trainee, through this lesson, trainee gain lot of information and through this experience it can be useful information in future. At PRISM, trainee was assigned special task to fulfill the industrial training requirement and the task given is trainee to done before the trainee finish the internship. Trainee must practice all the knowledge especially in Records Management fields.